THE CORRELATION AMONG STUDENTS’ READING INTEREST, READING COMPREHENSION, AND THEIR INTRALINGUAL TRANSLATION ACHIEVEMENT OF THE SIXTH SEMESTER STUDENTS OF ENGLISH DEPARTMENT OF STKIP MUHAMMADIYAH KOTABUMI, NORTH LAMPUNG IN THE ACADEMIC YEAR OF 2013/2014 - Rulik Setiani (ELTE Journal (English Languange Teaching and Education), 2014)
ABSTRACT  This research is a quantitative research which has the purpose to find out whether or not there was significant correlation among students’ reading interest, reading comprehension, and their intralingual translation achievement of the sixth semester students of English Education Department of STKIP Muhammadiyah Kotabumi, North Lampung in the academic year of 2013/2014. Furthermore, the population of the research is the sixth semester students of English Education Department of STKIP Muhammadiyah Kotabumi consisting of 120 students, from the population, 42 students were represented as the sample which was taken through simple random sampling technique. The instruments used were questionnaire for reading interest, multiple choice test for reading comprehension, and written test for intralingual translation. After having the result, then the data were analyzed by using multiple correlation  in SPSS 20 Program for Windows. From the result of the data analysis shows that Ryx1x2 = 0.655 at the significance level of 0.05, and for the criteria of significant test is gotten Fcount (37.037) > Ftable (4.08). So, the result of hypothesis test shows that there is significant correlation among students’ reading interest, reading comprehension, and their intralingual translation achievement of the sixth semester students of English Education Department of STKIP Muhammadiyah Kotabumi, North Lampung in the academic year of 2013/2014. Key words: Reading Interest, Reading Comprehension, and Intralingual Translation Achievement.